Dampak Kebijakan Penghapusan Kouta Impor dan Implikasinya terhadap Perlindungan Industri Nasional Presfektif Hukum Persaingan Usaha - Al Athif, Muhammad Alif; Hasan, Akhmad Farroh (Maliki Interdisciplinary Journal, 2025)
Indonesia’s policy of eliminating import quotas reflects its commitment to trade liberalization and global market integration. However, this policy raises concerns about the competitiveness and sustainability of the national industry, particularly within the competition law framework. This article systematically discusses how eliminating import quotas can affect the domestic market structure, lead to unfair competitive practices, and challenge domestic industry protection mechanisms. Using a normative and juridical approach, the article examines the relationship between free trade policies and the principle of fair business competition, as outlined in Law Number 5 of 1999. The discussion reveals that, without sufficient counterbalancing regulations, eliminating quotas can strengthen the dominance of foreign businesses, reduce the market share of local industries, and potentially create a disguised monopoly or oligopoly. Therefore, a synchronization policy is necessary to balance trade openness with the principle of fair business competition.